Evelyn Waugh’s War Novels in Francoist Spain - Cristina Zimbroianu (University of Bucharest Review. Literary and Cultural Studies Series, 2021)
Evelyn Waugh’s experiences as captain in the Second World War represented the raw material for several novels, such as Put out More Flags (1942), Men at Arms (1952) and Brideshead Revisited (1945). These novels depict, on the one hand, the experiences of once immature bright young people who are now confronting the war reality, and, on the other, they satirize the military bureaucracy and portray the nostalgia for the conservative age of Catholic English nobility, which disappeared during the war. It could be assumed that these three novels might have been well received in Franco’s Spain as the Catholic theme as well as Waugh’s right-wing conservative beliefs could have influenced the censors’ approval or disapproval. Thus, the present paper will analyse the reception in Spain of Put out More Flags, Men at Arms and Brideshead Revisited considering the reports enclosed in the censorship files guarded at AGA (General Archive of the Administration) in Alcalá de Henares, Madrid. These documents reveal that Waugh’s novels were not easily approved by the Spanish censors during the Francoist dictatorship.